Why estrogens matter for behavior and brain health. (May 2017) - Galea, Liisa A.M.; Frick, Karyn M.; Hampson, Elizabeth; Sohrabji, Farida; Choleris, Elena
Highlights: 17β-estradiol impacts specific cognitive and social behaviors in adult females. 17β-estradiol influences neuroprotection in models of stroke dependent on age. Estrone and 17β-estradiol differentially influence cognition and neuroplasticity. Experiential factors moderate cognitive outcome and neuroprotection with estrogens. Abstract: The National Institutes of Health (NIH) has required the inclusion of women in clinical studies since 1993, which has enhanced our understanding of how biological sex affects certain medical conditions and allowed the development of sex-specific treatment protocols. However, NIH's policy did not previously apply to basic research, and the NIH recently introduced a new policy requiring all new grant applications to explicitly address sex as a biological variable. The policy itself is grounded in the results of numerous investigations in animals and humans illustrating the existence of sex differences in the brain and behavior, and the importance of sex hormones, particularly estrogens, in regulating physiology and behavior. Here, we review findings from our laboratories, and others, demonstrating how estrogens influence brain and behavior in adult females. Research from subjects throughout the adult lifespan on topics ranging from social behavior, learning and memory, to disease risk will be discussed to frame an understanding of why estrogens matter to behavioral neuroscience.